Exploring the design of a sport for employability program: A case study - Commers, Tessa; Theeboom, Marc; Coalter, Fred (Frontiers in Sports and Active Living, 2022)
Rates of young people who are neither in employment, education, or training (NEET) are fairly high in the European Union. Correspondingly, there has been a growing tendency to regard sport as a suitable tool to develop soft skills and raise NEETs' level of employability. However, if and how such sport for employability (SfE) programs are able to realize these major claims has been called into question. The purpose of the present study was, therefore, to explore how an actual SfE initiative constructs and delivers its program. In addition, the article assessed whether the investigated program operates in line with researchers' recent calls for theory-based approaches. Guided by a case study approach set up within an initiative located in Flanders, data were gathered through 12 semi-structured interviews with 8 program providers. Results, analyzed using thematic analysis, indicated that the program was characterized by an absence of well-defined desired outcomes, imprecision as to how the program should contribute to these outcomes, and consequently minimal attention to the follow-up of participants' progress. As such, these findings and the accompanying challenges point to the absence of a theory-based approach. Several possible sources for the lack of a systematic approach are discussed.